Eco-physiological drivers of geographic range limits in two closely related euryhaline fish species - Marshall, Craig Anthony, author; Ghalambor, Cameron K., advisor; Angeloni, Lisa M., advisor; Myrick, Christopher A., committee member; Earley, Ryan L., committee member (Colorado State University. Libraries, 2021)
A fundamental goal in evolutionary ecology is to understand the problem of why species occur in some environments and not others. Indeed, a general pattern in nature is that many organisms occupy only a subset of the total range of the environments they are physiologically capable of tolerating. Theory suggests that the abiotic environment can constrain the distributions of species, but testing the relative roles of different mechanisms in shaping species distributions has proven to be a major challenge for both plants and animals. In fish, salinity tolerance is a defining factor in shaping the ranges of many species. Nonetheless, the influence of salinity tolerance on patterns of dispersal and local adaptation are understudied for most species. Euryhaline fishes are capable of acclimating to a wide range of salinities, yet may exhibit a preference for a particular salinity. For example, previous work in euryhaline teleosts indicates that crossing a salinity gradient typically results in increased oxygen uptake, energetic costs, and activation of the stress response. Thus, plastic or evolved tolerance to increased salinity might come at the expense of fitness-related traits (i.e., locomotion, feeding, mate acquisition, etc.), but few studies have investigated the potential for such trade-offs. Maintaining ionic and osmotic homeostasis in the face of a salinity change is critical for survival, but also energetically costly. Efficient osmoregulation relies primarily on the gills, but the process is complicated given that freshwater and saltwater fishes differ in the direction of ion transport through the gill epithelia. Thus, proper restructuring of the gills is fundamental to surviving a salinity transition. This plastic response has been observed in euryhaline fishes, however there is intra- and interspecific variation in the timescale of this process. The endocrine system plays a significant role in salinity acclimation, and in euryhaline teleosts salinity exposure increases the concentration of circulating plasma cortisol to facilitate osmoregulation. Previous work indicates that cortisol is involved in promoting structural changes in both fresh and saltwater gills, but its role in osmoregulation and adaptation differs between the two types. Thus, comparisons of cortisol concentrations can provide insight into the roles of local adaptation and plasticity for euryhaline fishes that exist along a salinity gradient. On the island of Trinidad, the euryhaline guppy (Poecilia reticulata) is confined to freshwater whereas the closely related swamp guppy (Poecilia picta), co-exists with the guppy in freshwater, but also spans into brackish and saltwater. To understand this pattern, we employed an integrative approach to investigate the mechanisms and potential trade-offs that may exist upon exposure to increased ambient salinity as a result of seasonal and daily tidal fluctuations. We examined the effect of a gradual salinity increase on sustained swimming (UCRIT) for P. reticulata and burst swim performance for P. reticulata and P. picta by estimating salinity performance curves (SPCs) using field collected fish. We mimicked the same salinity challenge in the lab and measured the ability of lab reared P. reticulata and P. picta to maintain internal osmolality. In addition, we used a novel method to quantify differences in circulating cortisol levels in P. picta allowing us to infer whether populations along the salinity gradient track stable versus variable salinity levels by adjusting their cortisol levels. Our experiments revealed that P. reticulata can maintain sustained swimming performance across a broad range of salinities and achieves peak performance at the isosmotic point, confirming its euryhaline ability. In contrast, both P. reticulata and P. picta initially experience a drop in burst swimming performance when exposed to salinity challenge, but are able to acclimate over time to higher salinities and re-establish their performance. However, this acclimation response occurs much more quickly in P. picta compared to P. reticulata. The slower acclimation response of P. reticulata could potentially make them more vulnerable to predation risk when they attempt to become established in brackish water, thus contributing to their ranges being restricted to freshwater in Trinidad. Cortisol analyses along the salinity gradient provide support for P. picta having the ability to plastically increase circulating cortisol levels in response to daily fluctuations in salinity. Overall, these results demonstrate how understanding the physiological responses to salinity can inform which mechanisms do and do not contribute to distribution patterns in nature.
Keywords: euryhaline fish; osmoregulation; eco-physiology; salinity; geographic range limits